2007
DOI: 10.1212/01.wnl.0000262763.66023.be
|View full text |Cite
|
Sign up to set email alerts
|

Psychological or physiological

Abstract: Despite severe physical impairment and disability and frequent medical complications, subjects with complete spinal cord injury at high anatomic levels report better than average quality of life, being overall content. Reasons for these findings are unclear. Psychological adaptive reactions are likely, but the possible role of physiologic and neurocognitive changes needs further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 37 publications
3
21
2
Order By: Relevance
“…4,5 This finding supports the notion that disability and health are separate constructs, and is consistent with the literature on disability and quality of life which documents high subjective quality-of-life ratings even for individuals who are severely disabled. 18,[29][30][31][32] Consistent with other literature on SRH, we found that individuals reporting more health conditions also rated their health as less robust. Health conditions have been recognized as a strong predictor of SRH among the general population 23,24 as well as disabled populations.…”
Section: Discussionsupporting
confidence: 90%
“…4,5 This finding supports the notion that disability and health are separate constructs, and is consistent with the literature on disability and quality of life which documents high subjective quality-of-life ratings even for individuals who are severely disabled. 18,[29][30][31][32] Consistent with other literature on SRH, we found that individuals reporting more health conditions also rated their health as less robust. Health conditions have been recognized as a strong predictor of SRH among the general population 23,24 as well as disabled populations.…”
Section: Discussionsupporting
confidence: 90%
“…2 SCI and MT often cause severe disabilities and dramatic changes in the life of the afflicted person and are usually associated with reduced functional health levels. 2,3 The findings are not unequivocal, however. For example, several studies suggest that health-related quality of life after SCI or MT is not always influenced by the severity of either impairment or disability.…”
Section: Introductionmentioning
confidence: 90%
“…For example, several studies suggest that health-related quality of life after SCI or MT is not always influenced by the severity of either impairment or disability. 3,4 The causes of these findings are unclear, but it is assumed that psychological adaptive responses are involved. 3 Previous research on SCI and MT populations has included a variety of functional health determinants, such as demographic factors and co-morbidity, 2 physical fitness 5 and social support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is less likely for subjective QoL in which even those with high level complete tetraplegia have been reported to be very satisfied with their lives. 6 However to date, the focus of most studies of the QoL of people with an SCI has been on those with T-SCI. [7][8][9][10] Few study samples have included people with NT-SCI; 11,12 however, those studies did not differentiate between aetiologies in their analyses.…”
Section: Introductionmentioning
confidence: 99%